Textual Poaching Dalam Industri Budaya K-Pop Oleh Penggemar sebagai Prosumer - Sari, Rizka Annisa; Salsabila, Arini; Alinda, Yunati; Nurhaliza, Adinda Aulia (Jayapangus Press, 2025)
The K-Pop industry as a form of subculture within popular culture, offers more than just analysis focused on artists and their music, but also consider the aspect of it fans. In Indonesia, K-Pop is one of the most popular genres and receives high enthusiasm, especially due to the participation of it fans in promoting it by consuming and producing K-Pop-themed cultural texts. This study explores the Indonesian K-Pop fans as prosumers within the cultural industries through the practice of textual poaching. Using a qualitative approach with constructivist paradigm, data were collected through interviews with four K-Pop fans actively involved in producing fan art, fan fiction, and fan edits. The prosumer theories of Alvin Toffler and Henry Jenkins are applied to examine the blurred lines between producers and consumers in participatory culture. Findings reveal that fans do not merely consume cultural texts but also reconstruct and redistribute new meanings based on personal preferences, demonstrating their creative autonomy. Although some gain material benefits, most of these activities are carried out voluntarily and are regarded as hobbies, so they are unaware of the subtle element of free labour in the activities they engage in. The study supports the perspective of French cultural sociologists that the cultural industry is ambivalent, contested, and open to bottom-up innovation (grassroots creativity). Recommendations for further research could use a critical paradigm and specifically examine fans at the worker level, to better align with theories in the cultural industries.